Flexor tendon injury: Avascular or vascularized region suture? Biomechanical and histopathological study in rabbits - Sardenberg, Trajano [UNESP]; Muller, Sergio Swain [UNESP]; Coelho, Kunie Iabuk Rabello [UNESP]; Varanda, Denis [UNESP]; Cortopassi, Andrea Christina [UNESP]; Pereira, Gilberto José Cação [UNESP] (Thieme, 2019)
Objectives To analyze the mechanical and histopathological aspects of flexor tendon healing with interest on the site of the placement of the suture, either in the vascular or in the avascular region. Methods A total of 83 rabbits were submitted to the Kessler type central suture in the vascularized tendon region (TN group) and in the avascular tendon region (FC group). The operated limb was immobilized for 3 weeks. The animals were sacrificed in the immediate postoperative period, and at 2, 3 and 6 weeks postoperatively. The mechanical properties studied were: maximum load, maximum load stress, modulus of elasticity, energy at maximum load, and energy per area. The contralateral tendon was used as control. The histopathological study was descriptive. Results The analysis of the mechanical properties showed similar behavior in both groups, with stabilization or discrete increase in the immediate period at 3 weeks and a marked increase at 6 weeks. Histopathology demonstrated a similar healing process in the TN and FC groups. Conclusion Placement of the central suture in the vascularized or avascular fibro-cartilaginous region presents no differences in biomechanical and histopathological aspects in the healing of the flexor tendon in rabbits.
Lesão do tendão flexor: sutura na região avascular ou vascularizada? Estudo biomecânico e histopatológico em coelhos
Keywords: Rabbits; Sutures; Tendon injuries